Sleep spindle and slow wave frequency reflect motor skill performance in primary school-age children - Astill, Rebecca G.; Piantoni, Giovanni; Raymann, Roy J. E. M.; Vis, Jose C.; Coppens, Joris E.; Walker, Matthew P.; Stickgold, Robert; Van Der Werf, Ysbrand D.; Van Someren, Eus J. W. (Frontiers in Human Neuroscience, 2014)
Background and Aim. The role of sleep in the enhancement of motor skills has been been studied extensively in adults. We aimed to determine involvement of sleep and characteristics of spindles and slow waves in a motor skill in children. Hypothesis. We hypothesized sleep-dependence of skill enhancement and an association of interindividual differences in skill and sleep characteristics. Methods. 30 children (19 females, 10.7±0.8 years of age; mean±SD) performed finger sequence tapping tasks in a repeated-measures design spanning 4 days including 1 polysomnography night. Initial and delayed performance were assessed over 12 hours of wake; 12 hours with sleep; and 24 hours with wake and sleep. For the 12 hours with sleep, children were assigned to one of three conditions: modulation of slow waves and spindles was attempted using acoustic perturbation, and compared to yoked and no-sound control conditions. Analyses. Mixed effect regression models evaluated the association of sleep, its macrostructure and spindles and slow wave parameters with initial and delayed speed and accuracy. Results and Conclusions. Children enhance their accuracy only over an interval with sleep. Unlike previously reported in adults, children enhance their speed independent of sleep, a capacity that may to be lost in adulthood. Individual differences in the dominant frequency of spindles and slow waves were predictive for performance: children performed better if they had less slow spindles, more fast spindles and faster slow waves. On the other hand, overnight enhancement of accuracy was most pronounced in children with more slow spindles and slower slow waves, i.e. the ones with an initial lower performance. Associations of spindle and slow wave characteristics with initial performance may confound interpretation of their involvement in overnight enhancement. Slower frequencies of characteristic sleep events may mark slower learning and immaturity of networks involved in motor skills.